1997
DOI: 10.1093/emboj/16.15.4698
|View full text |Cite
|
Sign up to set email alerts
|

Ikappa Balpha -independent downregulation of NF-kappa B activity by glucocorticoid receptor

Abstract: IκBα is an inhibitor protein that prevents nuclear transport and activation of the transcription factor NF‐κB. In acute inflammation, NF‐κB is activated and increases the expression of several pro‐inflammatory cytokine and chemokine genes. Glucocorticoids counteract this process. It has been proposed that the glucocorticoid‐dependent inhibition of NF‐κB activity is mediated by increased synthesis of IκBα which should then sequester NF‐κB in an inactive cytoplasmic form. Here, we show by the use of a mutant glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(158 citation statements)
references
References 64 publications
8
148
1
1
Order By: Relevance
“…For example, induction of glutamine synthase by GR-LS7 was very low (Figure 1), as described previously , but induction of IkBa by GR-LS7 (Table 1,`MAD-3'), as previously shown by Northern blotting (Heck et al, 1997) was comparable to the degree of induction seen in GR-wt. Of potential importance for this discrepancy, Scheinman et al (1995) reported no functional GREs in the MAD-3 (IkBa) promoter.…”
Section: Resultssupporting
confidence: 84%
“…For example, induction of glutamine synthase by GR-LS7 was very low (Figure 1), as described previously , but induction of IkBa by GR-LS7 (Table 1,`MAD-3'), as previously shown by Northern blotting (Heck et al, 1997) was comparable to the degree of induction seen in GR-wt. Of potential importance for this discrepancy, Scheinman et al (1995) reported no functional GREs in the MAD-3 (IkBa) promoter.…”
Section: Resultssupporting
confidence: 84%
“…Repression occurred independently of the GR dimerization and DNA binding function and did not involve IkB synthesis in these cells . It thus seems that glucocorticoids do not induce IkB in all cell types and the induction of IkB is not required for transrepression of NF-kB (see also Heck et al, 1997;Dumont et al, 1998).…”
Section: Tethering Mechanismsmentioning
confidence: 99%
“…Poly(A) + RNA preparation and Northern blots were carried out essentially as described by Heck et al (1997).…”
Section: Rna Preparation and Northern Blot Analysismentioning
confidence: 99%